Immigrants in a booming economy: analysing their earnings and welfare dependence - Alan Barrett; Yvonne McCarthy (Institute for the Study of Labor (IZA), 2006)
Ireland's exceptional economic growth in recent years has led to an influx of immigrants. Given the favourable economic climate into which these immigrants are arriving, it is interesting to ask how their earnings and welfare dependence compare with the native population. To the extent that strong economic growth produces good labour market opportunities for immigrants, earnings disadvantages may be lessened and any tendency towards welfare dependence may be reduced. Data from a nationally representative sample drawn in 2004 are used to assess the earnings of immigrants in Ireland relative to the native population and also the rate of welfare receipt across the two groups. Immigrants are found to earn 18 percent less than natives, controlling for education and years of work experience. However, this single figure hides differences across immigrants from English-speaking and non-English speaking countries. We also find evidence of a wage gap for immigrants with third level educations, relative to comparable natives. On average, immigrants are half as likely to have been in receipt of social welfare payments in the previous twelve months relative to natives. A difference in welfare participation remains when we control for the higher education attainment of immigrants.
urn:nbn:de:101:1-20080702231
Keywords: 330